RISPÁ simplesmente RISPÁ - Weiler, Lucia (2013)
This article seeks to recover a literary pearl, hidden in the larger story of the time of the monarchy, registered in the Bible. It is the presence of Rizpah, as the name is translated in some editions of the Bible. This presence, with its untold story, breaks away from the story of violence, weaving fine, strong threads in the small-great story of liberation. Rizpah questions the image of a violent God who is satisfied with violence. She proclaims a God, silent presence among the innocent whose bodies and human dignity have been violated.